Determinants of Bottle-Feeding: Experience in a Tertiary Care Hospital (Jalalabad Medical Journal, 2025)
Feeding practice is crucial in a child's life. Many women don't know that giving infants bottle-feeding has consequences. Though bottle-feeding practice is discouraged among mothers, the use of bottles in infant feeding practice is still high. The objective of this study was to assess the determining factors for bottle-feeding in one- to twelve-month-old infants admitted to the paediatric ward at Jalalabad Ragib-Rabeya Medical College Hospital between the periods of January 2018 to June 2018. For this purpose, 128 mothers were purposively interviewed. A pre-formed questionnaire was used for data collection. Infants' and mothers' demographic variables and feeding practices were documented and analysed. Bottle-feeding is more com mon in older infants (10-12 months). Infants born in private clinics and with caesarean sections were more likely to feed bottles (p